Analisis Determinan Pertumbuhan Laba Padaperusahaan Makanan Dan Minuman Yangterdaftar Di Bursa Efek Indonesia - Qahfi Romula Siregar; Muhammad Fakhri Gurning; Jumeida Simatupang (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2020)
Companies should be able to optimize existing resources because growth has an important role in working capital management. By knowing how much growth, a company should be able to predict how much profit it will get. So that the relationship between company performance and value creation for shareholders with sales growth has become an investment goal. In accordance with the problems raised in the study, the purpose of this study is to empirically prove the influence of Total Assets Turnover on Profit Growth in Food and Drink Companies that are listed on the Indonesia Stock Exchange. To empirically prove the effect of Sales Growth on Profit Growth in Food and Drink Companies registered in the Indonesia Stock Exchange. To prove empirically the effect of Total Assets Turnover and Sales Growth together on Profit Growth in Food and Drink Companies registered in the Indonesia Stock Exchange. Based on the results of research that partially there is a significant influence of Total Assets Turnover on Profit Growth. Partially there is a significant effect of Sales Growth on Profit Growth. Simultaneously there is the influence of variable Total Assets Turnover, Sales Growth on Profit Growth.